Pedagogia dos movimentos sociais: as manifestações de 2013 como espaço de aprendizado - Rosa, Roberta Soares da (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation aims to understand the educational dimensions in the collective actionsprocesses stimulated by Porto Alegre Public transportBlock Struggles. The methodology used was the systematization of experiences from the perspective of participatory research, through individual interviews, conversation circles and netnography.The theoretical backgroundwas built from Maria da GlóriaGohn, Paulo Freire, Alberto Melucci, Ilse Scherer-Warren, Manuel Castells, André Lemos, Hugo Assman, DaniloStreck, among others.In this sense, we propose to reflect on the changes that have been happening in the social movements on how to organization and communication and these movements provide some learning to its participants. We conclude that the Fights Block provides intentional training spaces as public classes, however, the subjects identified as the main training area militancy of experience in street protests, meetings and occupations. We identify indicators that the Block promotes awareness of the subject, because it has participants committed to the reality in the search for a more just and equal world, staying involved in social causes that go beyond this mobilization organization. Social media appear as strong characteristic of this type of movement, essential for communication and mobilization of the subjects, however the difficulty of pedagogical mediationbrings some limitations in its use.
Keywords: Movimentos sociais; Participação; Mídias sociais; Mobilizações de 2013; Social movements; Participation; Social media; 2013 mobilizations; ACCNPQ::Ciências Humanas::Educação